2014
DOI: 10.1159/000360910
|View full text |Cite
|
Sign up to set email alerts
|

Management of Insomnia in Traditional Persian Medicine

Abstract: Insomnia is a sleep disorder which affects 10-48% of general population. Different measures, such as pharmacotherapy and behavioral management, are applied for insomnia and associated complaints. In traditional medical systems, herbal medicines are considered beneficial. Therefore, the present paper compiles pharmacological and medical insights into the management of insomnia according to Traditional Persian Medicine. Herein, preserved medical and pharmaceutical manuscripts of Persian medicine from 10th to 18t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It is to be mentioned that in addition to pharmacotherapy, massage therapy is also applied in TPM (usually accompanied by anointment) for management of insomnia [20]. This usually includes foot massage which has a stress reduction effect, too.…”
Section: Signs and Symptoms Treatmentmentioning
confidence: 99%
“…It is to be mentioned that in addition to pharmacotherapy, massage therapy is also applied in TPM (usually accompanied by anointment) for management of insomnia [20]. This usually includes foot massage which has a stress reduction effect, too.…”
Section: Signs and Symptoms Treatmentmentioning
confidence: 99%
“…[9091] Different measures, such as pharmacotherapy and behavioral management, are applied for insomnia and associated complaints. [92] Current insomnia pharmacotherapeutic agents mainly target the γ-aminobutyric acid (GABA) receptor, melatonin receptor, histamine receptor, orexin, and serotonin receptor. GABA receptor modulators are ordinarily used to manage insomnia, but they are known to affect sleep maintenance, including residual effects, tolerance, and dependence.…”
Section: Clinical Studies Done On Polygonum Multiflorum And/or Its Bimentioning
confidence: 99%
“…It should be noted that treatments that have been used over centuries may provide a significant pathway for clinical research (Hashempur, Khademi, Rahmanifard, & Zarshenas, ; Petramfar, Zarshenas, Moein, & Mohagheghzadeh, ). Specifically, an analysis by the National Health Administration of the United States found that 4.5% of adults in the United States used complementary and alternative medicine for the treatment of insomnia and their sleeping problems over the past 12 months (Lin et al, ).…”
Section: Introductionmentioning
confidence: 99%